PENGARUH DISIPLIN DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. SWADHARMA SARANA INFORMATIKA BEKASI - Dedek Dafva Ukiraningsyah; Shella Puspita Sari (Journal of Research and Publication Innovation, 2025)
This study aims to determine the effect of discipline and work environment on employee performance at PT. Swadharma Sarana Informatika both partially and simultaneously on the processing of empirical data from the distribution of questionnaires that have been carried out. The method used in this study is a quantitative method using a sampling technique of 80 respondents. In this study using data analysis techniques in the form of: validity testing, reliability testing, normality testing, classical assumption testing, quantitative testing and hypothesis testing. It can be seen that the results of the multiple linear regression equation obtained between Ŷ = 7.416 + 0.410 (X1) + 0.397 (X2). This is evidenced by the results of the hypothesis test based on the simultaneous F value obtained > F table or (60.821 > 3.120), this is also strengthened by the significance <0.050 or (0.000 <0.050). The results of the coefficient of determination test of the discipline variable (X1) and work environment (X2) have an influence of 61.2% on performance at PT. Swadharma Sarana Informatika. Thus Ho is rejected Ha is accepted, it can be interpreted that there is a significant simultaneous influence between discipline (X1) work environment (X2) on employee performance (Y).